HLA-G Genotype/Expression/Disease Association Studies: Success, Hurdles, and Perspectives - Amodio, Giada; Gregori, Silvia (Frontiers in Immunology, 2020)
The non-classical HLA-G is a well-known immune-modulatory molecule. In physiological condition HLA-G surface expression is restricted to the maternal-fetal interface and to immune-privileged adult tissues, whereas soluble forms of HLA-G are detectable in various body fluids. HLA-G can be de novo expressed in pathological conditions including tumors, chronic infections or after allogeneic transplantation. HLA-G exerts positive effects modulating innate and adaptive immune responses and promoting tolerance, or detrimental effects inducing immune escape mechanisms. HLA-G locus, in contrast to classical HLA class I gene, is highly polymorphic in the non-coding 3' un-translated region (UTR) and in the 5’ upstream regulatory region (5’URR). Variability in these regions influences HLA-G expression by modifying mRNA stability or allowing post-transcriptional regulation in the case of 3’UTR, or by sensing the microenvironment and responding to specific stimuli in the case of HLA-G promoter regions (5’URR). The influence of genetic variations on the expression of HLA-G makes it an attractive biomarker to monitor disease predisposition and progression, or response to therapy. Here, we will summarize the current knowledge, efforts, and obstacles to generate a general consensus on the correlation between HLA-G genetic variability, protein expression and disease predisposition. Moreover, we will discuss perspectives for future investigation on HLA-G genotype/expression in association with disease predisposition and progression.